Molecular Dynamics Modeling of Bonding Two Materials by Atomic Scale Friction Stir Welding at Different Process Parameters; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Konovalenko I. S. Ivan Sergeevich (2017, 2017)
Title screen